Elaboración y estudio de la variación del porcentaje de proteinas en salchichas de camarón crudo y cocido - Ortega Balbuco, Diana Carolina (2014)
To carry out the investigation the muscle of shrimp of the variety ointment it was used, for the prosecution of the sausage the laundry methodology was continued, drained, dive, ground, addition of the ingredients, sausage and cooking,, following the regulatory schemes that he/she gives the Good ones Practices of Factories, obtaining this way 10 samples for the proposal of raw sausage and 10 samples for the sausage cooked, of the same ones they took the enough samples to carry out the organoleptic, chemical analyses and microbiologic, also they were subjected to a direct survey to the consumer. The results obtained in the sausages of raw shrimp, the protein levels are low, but in any event they continue being superior to the requirements for the INEN (1996) for the raw sausages where it points out that this product should have a minimum of 12% protein, therefore it can make sure that the shrimp sausage is more nutritious than the preparation with pig meat. The results obtained in the sausages of shrimp cooked, the protein levels are low, but in any event they continue being superior to the requirements for the INEN (1996), where it points out that this product should have a minimum of 12 protein%, but it fulfills the report of Dietplan (2000) that indicates that the Viennese sausage contains among the 10.8 to 12.5% protein. For the organoleptic characteristics in sausage of raw shrimp one had: scent 70% corresponds to lightly perceptible (4), texture 70% that corresponds to soft (4), flavor 70% represents to the very good parameter (5), colour 60% represents to the very good parameter (5) and appearance 50% represents to the very good parameter (5), and 50% corresponds to good (4). For the organoleptic characteristics in sausage of raw shrimp was obtained: scent 70 lightly perceptible% (4), texture 80% represents to half hard (3), flavor 60% corresponds to the characteristic good parameter (4), colour 40% represents to the very good parameter (5), 40% corresponds pleasant (4) 20 good% (3) and appearance 60% represents to the very good parameter (5). For I finish for the acceptability of raw sausage and cooked that it was qualified by the unpleasant, not very unpleasant, indifferent, pleasant and very pleasant parameters obtaining a result of 80% of those interviewed they consider excellent to the raw sausage, 20 very good% and the sausage cooked had 50% of excellent and 50% of very good. For what you concludes that: the content of proteins in the raw sausage, their nutritious contribution overcomes to the minimum requirements demanded by the INEN (1996), in its norm NTE INEN 1 338:96. The content of proteins in the sausage cooked, their nutritious contribution is inferior to the minimum requirements demanded by the INEN (1996), in its norm NTE INEN 1 338:96. But it fulfills the nutritional report of Dietplan(2000). The bacteriological quality of the sausages was obtained the absence of pathogen microorganisms, being considered a capable product for the human consumption. With regard to the organoleptic characteristics, they received a qualification of excellent for the raw and very good sausage for the sausage cooked having bigger acceptance for those interviewed the raw sausage. According to the obtained results it is recommended: To elaborate shrimp sausages with different formulation, adding products protein, with the purpose of not affecting the content of proteins. To promote this type of innovative products as the shrimp sausage in the local, regional and national market. To elaborate sausages of raw shrimp and cooked with different percentages of starch of corn, and to determine which gives a higher level in proteins, To evaluate the useful life of the shrimp sausage whereas this product can be defective if they don't take the correct conservation measures.